The association between exposure to food marketing and dietary intake among youth in six countries - Vergeer, Laura; Gillis, Grace; Rynard, Vicki L.; Vanderlee, Lana; White, Christine M.; Nieto, Claudia; Hammond, David; Potvin Kent, Monique (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background While food marketing to youth is associated with harmful behavioural and dietary outcomes, few studies have assessed differences in this relationship between countries. This study examined the association between exposure to food marketing and dietary intakes among youth in six countries. Methods A cross-sectional analysis of International Food Policy Study 2023 Youth Survey data examined the relationship between self-reported exposure to marketing for less healthy (fast food, sugary drinks, sugary cereals, snacks, desserts/treats) and healthy (fruits, vegetables) food categories across various media/settings in the past 30 days and consumption of these foods yesterday among youth 10-17 years-old in Canada, Australia, Chile, Mexico, the United Kingdom and the United States (n=9057). Associations of food consumption with exposure to marketing of food categories and marketing techniques (e.g., characters, famous people) in food advertisements, and differences in associations between countries, were examined using binary and ordinal logistic regression. Results In all countries, youth reporting more frequent exposure to marketing of all less healthy food categories had higher odds of having consumed those foods yesterday (p < 0.05 for all), except snacks in Mexico. Compared with no exposure to marketing techniques, exposure to ≥ 1 marketing technique(s) in less healthy food advertisements was associated with higher odds of having consumed sugary drinks (AOR: 1.44; 95% CI: 1.21, 1.72), fast food (AOR: 1.69; 95% CI: 1.40, 2.03), sugary cereals (AOR: 1.26; 95% CI: 1.05, 1.51) and desserts/treats yesterday (AOR: 1.42; 95% CI: 1.18, 1.71) among youth in all countries. Consumption of snacks was associated with exposure to ≥ 1 marketing technique(s) in less healthy food advertisements in Australia (AOR: 1.61; 95% CI: 1.09, 2.34), Chile (AOR: 1.63; 95% CI: 1.12, 2.36) and Mexico (AOR: 2.13; 95% CI: 1.39, 3.26). Positive associations between frequency of exposure to marketing of fruits and vegetables and the number of times these foods were consumed yesterday were observed in all countries (p < 0.05), except vegetable consumption in the UK. Conclusions These results support the association between exposure to food marketing and consumption of marketed foods. Findings were similar between countries, reinforcing the need for global implementation of restrictions on food marketing to youth.